Link Between Topographic Memory and the Combined Presentation of ADHD (ADHD-C): A Pilot Study - Faedda, Noemi; Guariglia, Cecilia; Piccardi, Laura; Natalucci, Giulia; Rossetti, Serena; Baglioni, Valentina; Alunni Fegatelli, Danilo; Romani, Maria; Vigliante, Miriam; Guidetti, Vincenzo (Frontiers in Psychiatry, 2021)
Background: Topographic memory is the ability to reach various places by recognizing spatial layouts and getting oriented in familiar environments. It involves several different cognitive abilities, in particular executive functions (EF), such as attention, working memory, and planning. Children with Attention Deficit Hyperactivity Disorder (ADHD) show impairments in inhibitory control, regulation of attention, planning and working memory. Aim: The aim of this study was to evaluate the topographic memory in children with ADHD-Combined subtype (ADHD-C). Method: 15 children (8-10yrs) with a diagnosis of ADHD-C, (DSM-5) (ADHD-C Group) have been compared to 15 children with typical development (TD Group)of the same age. All children performed the Raven’s CPM to obtain a measure related with cognitive functioning. The Walking Corsi Test (WalCT) a large-scale version of the Corsi Block-Tapping Test, was used to assess topographic memory in experimental environment. Results: A higher impairment in ADHD-C than TD with significantly differences in the WalCT, in particular: on the Topographic Short Term Memory (TSTM), on the Topographic Learning (TL) task and on the Repetition Number (RN) during the TL task. Perseverative errors were reported in performing the square-sequence in WalCT. Zero order correlations showed a positive correlation between TSTM and Auditory Attention, and Memory of Design of NEPSY-II and Digit Span of WISC-IV. No statistically significant differences were found between ADHD-C group and TD group in TL task in WalCT condition. Conclusion: in ADHD-C, initial topographic learning resulted compromised whereas the long-term retention of learned topographical material seemed to be not impaired. In particular, these impairments seem to be linked with difficulties in the sustained attention, in spatial memory for novel visual materials, in a poor working memory, and in perseverative behaviours.